1868-69 N.C. Sess. Laws 202 - (:unkn) unknown (My University, 1868)
Priv. Laws, ch. 123, § 18: Granted the Board the power to levy and collect taxes on all pistols, except when part of stock in trade. Also on all dirks, Bowie-knives, and sword-canes if worn on the person at any time during the year. Tax not to exceed one dollar.
Keywords: TAX - PROPERTY OR SALES